Effects of Spot Diameter and Sheets Thickness on Fatigue Life of Spot Welded Structure based on FEA Approach - M. M., Rahman; R. A., Bakar; M. M., Noor; M. S. M., Sani; J. M., Julie (2009)
This study presents the effect of the spot weld and sheets thickness on the fatigue life of the of the spot-weld joints to predict the lifetime and location of the weakest spot-welds due to the variable amplitude loading conditions. A simple model was used to illustrate the technique of spot-weld fatigue analysis. Finite element model and analysis were carried out utilizing the finite element analysis commercial codes. Linear elastic finite element analysis was carried out to predict the stress state along the weld direction. It can be seen from the results that the predicted life greatly influence the sheet thickness, nugget diameter and loading conditions of the model. Acquired results were shown the predicted life for the nugget and the two sheets around the circumference of the spot-weld at which angle the worst damage occurs. The spot-welding fatigue analysis techniques are awfully essential for automotive structure design.